The Effect of Economic Growth, Unemployment, Wages and Labor on Poverty in The Pati Ex-Resident in 2017-2021: Pengaruh Pertumbuhan Ekonomi, Pengangguran, Upah dan Tenaga Kerja Terhadap Kemiskinan di Eks- Karesidenan Pati Tahun 2017-2021 - Dewi, Reny Fitria; Setyowati, Eni (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to determine the magnitude of the influence of the variables of economic growth, unemployment rate, wages and labor on poverty in the Pati Ex-Resident which consists of 6 regencies in 2017-2021. Poverty as the dependent variable, and economic growth, unemployment, wages and labor as independent variables. The analytical technique used is panel data regression analysis using the Eviews 10 program computer. This study uses secondary data obtained from the Central Statistics Agency (BPS) for a period of 5 years starting from 2017-2021 and the National Journal as a supporter. This research is expected to be a consideration for policy making for the central government, especially local governments in tackling poverty levels so that the economy progresses.